The role of memory in affirming-the-consequent fallacy - Yoko Higuchi; Ethan Oblak; Hiroko Nakamura; Makiko Yamada; Kazuhisa Shibata (iScience)
Summary: People tend to recognize that a transitive relation remains true even when its order is reversed. This affirming-the-consequent fallacy is thought to be uniquely related to human intelligence. It is generally thought that this fallacy is a byproduct of explicit reasoning at the moment of recognition of the reversed order. Here, we provide evidence suggesting a reconsideration of this account using an implicit memory paradigm, which minimizes the involvement of explicit reasoning. Specifically, we tested a two-stage memory model: (1) when a sequence of events is encoded, the memory of the reversed sequence is formed, resulting in the affirming-the-consequent fallacy, and (2) the memories of the forward and reversed sequences are integrated over time, reinforcing the fallacy. Results of behavioral and functional magnetic resonance imaging experiments were consistent with this memory-based model. Our findings suggest that the affirming-the-consequent fallacy may begin unwittingly when individuals memorize a transitive relation.